2008
DOI: 10.1128/mcb.01858-07
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Aγ-Globin Gene Expression during Adult Definitive Erythropoiesis Mediated by GATA-1-FOG-1-Mi2 Complex Binding at the −566 GATA Site

Abstract: Autonomous silencing of ␥-globin transcription is an important developmental regulatory mechanism controlling globin gene switching. An adult stage-specific silencer of the A ␥-globin gene was identified between ؊730 and ؊378 relative to the mRNA start site. A marked copy of the A ␥-globin gene inserted between locus control region 5 DNase I-hypersensitive site 1 and the -globin gene was transcriptionally silenced in adult ␤-globin locus yeast artificial chromosome (␤-YAC) transgenic mice, but deletion of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(91 citation statements)
references
References 81 publications
5
86
0
Order By: Relevance
“…[4][5][6][7][8][9][10][11] Although under tight transcriptional control, the g-globin genes are also modulated by translational events. For example, sickle cell patients treated with butyrate had rapid increases in HbF levels in reticulocytes supporting g-globin regulation independent of transcriptional activation 12 implicating translational mechanisms of control.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] Although under tight transcriptional control, the g-globin genes are also modulated by translational events. For example, sickle cell patients treated with butyrate had rapid increases in HbF levels in reticulocytes supporting g-globin regulation independent of transcriptional activation 12 implicating translational mechanisms of control.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that NuRD complexes play critical roles within specific subsets of hematopoietic cells, for example, in megakaryocyte differentiation, 15,16 T-and B-lymphocyte development, [17][18][19][20] erythroid differentiation, [21][22][23][24] and adult bone marrow hematopoiesis. 25 However, it is not known whether NuRD complexes are involved in primitive hematopoiesis.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has provided evidence that the silencing function of this promoter region is exerted by the binding of a protein complex containing GATA-1, FOG-1, and Mi2 at the −566/−567 GATA site [74].…”
Section: Regulation Of γ-Globin Gene Expressionmentioning
confidence: 99%